Carbapenem-resistant Enterobacteriaceae (CRE) and gram-negative bacterial infections in south-west Nigeria: a retrospective epidemiological surveillance study - Oluwafolajimi Adetoye Adesanya; Hilda Amauche Igwe (AIMS Press, 2020)
Background Carbapenem-resistant Enterobacteriaceae (CRE) are often responsible for severe, life-threatening infections and they represent a critical threat to the available antibiotic agents and to global health. An understanding of the epidemiology of these infections will be indispensable to the development of appropriate case management as well as infection prevention and control (IPC) measures in any healthcare setting. Objectives The objective of this study was to investigate and describe the epidemiology of carbapenem-resistant Enterobacteriaceae (CRE) and other gram-negative bacteria in a tertiary hospital in south west Nigeria using routinely collected microbiological laboratory data. Methods A retrospective collection of microbiological laboratory records from the January to June 2018 was performed. All culture and antimicrobial susceptibility test results of patients who required laboratory tests were collected. Other information collected include: patient demographics, clinical specimen types and the requesting hospital department. The data was analyzed using SPSS Windows version 24. Comparison between categorical variables was done using chi-square tests while independent sample t-test was used to determine significant mean differences between groups. A p < 0.05 was taken to be statistically significant. Results The prevalence of carbapenem-resistance among Enterobacteriaceae and gram-negative bacteria isolates was 22% (n = 39/177). Of these, 35.9% (n = 14) were Klebsiella pneumonia, 30.8% (n = 12) were Pseudomonas aeruginosa and 15.4% (n = 6) were Klebsiella oxytoca. 87.2% (n = 34) of these were also multi-drug resistant, with a mean total resistance score of 3.92 (SD = ± 1.44). There were differences observed in proportion of carbapenem-resistance across clinical specialties and age groups; however, these differences were not statistically significant. Independent sample t-test revealed that carbapenem-resistant isolates exhibited more drug resistance than carbapenem-sensitive isolates (3.93 vs. 2.30; p < 0.001). Conclusion Carbapenem resistance is an important threat to the current antibiotic armory. Active surveillance, particularly in the healthcare setting is required to identify high risk groups, inform better treatment options and infection prevention and control measures.